The soluble guanylate cyclase activator cinaciguat prevents cardiac dysfunction in a rat model of type-1 diabetes mellitus - Mátyás, Csaba; Németh, Balázs Tamás; Oláh, Attila; Hidi, László; Birtalan, Ede; Kellermayer, Dalma; Ruppert, Mihály; Korkmaz-İçöz, Sevil; Kökény, Gábor; Horváth, Eszter Mária; Szabó, Gábor; Merkely, Béla; et al. (Cardiovascular diabetology, 2015)
Diabetes mellitus (DM) leads to the development of diabetic cardiomyopathy, which is associated with altered nitric oxide (NO)—soluble guanylate cyclase (sGC)—cyclic guanosine monophosphate (cGMP) signalling. Cardioprotective effects of elevated intracellular cGMP-levels have been described in different heart diseases. In the current study we aimed at investigating the effects of pharmacological activation of sGC in diabetic cardiomyopathy.